2019
DOI: 10.1108/pijpsm-08-2018-0110
|View full text |Cite
|
Sign up to set email alerts
|

Understanding public satisfaction with the police

Abstract: Purpose Building upon prior research, the purpose of this paper is to improve the understanding of public satisfaction with the police by examining the effects of one’s military background and the interactions between one’s education and perceptions about prior contact with the police. Design/methodology/approach This study statistically analyzes the 2012 citizen survey data collected in the Hampton Roads area of Virginia, USA, and the theoretical framework includes the major models of citizen satisfaction w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…There is abundant literature on public perceptions of police in large developed and developing countries (Ajayi & Longe, 2015; Awan et al, 2019; Boateng, 2012; Dai et al, 2019; Gau, 2010; Jiang et al, 2012; Lum et al, 2021; Wu, 2009). However, there is scant literature on public perceptions of police in the context of Small Island Developing States (SIDS) and particularly in the Pacific Island Countries (PICs; Bull et al, 2021; Dinnen, 2019; Dinnen & Watson, 2021; Howes et al, 2021; McLeod, 2009; McLeod & Dinnen, 2007; Watson & Dinnen, 2020; Watson, Amin, & Pino, 2021; Watson, Boateng, & Miles-Johnson, 2021, Watson, Sousa-Santos, & Howes, 2021; Watson & Johnson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There is abundant literature on public perceptions of police in large developed and developing countries (Ajayi & Longe, 2015; Awan et al, 2019; Boateng, 2012; Dai et al, 2019; Gau, 2010; Jiang et al, 2012; Lum et al, 2021; Wu, 2009). However, there is scant literature on public perceptions of police in the context of Small Island Developing States (SIDS) and particularly in the Pacific Island Countries (PICs; Bull et al, 2021; Dinnen, 2019; Dinnen & Watson, 2021; Howes et al, 2021; McLeod, 2009; McLeod & Dinnen, 2007; Watson & Dinnen, 2020; Watson, Amin, & Pino, 2021; Watson, Boateng, & Miles-Johnson, 2021, Watson, Sousa-Santos, & Howes, 2021; Watson & Johnson, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…That is, when a suspect views law enforcement as fair, moral, and just, they are less likely to question police authority or to resist it (Tyler, 1990). Along these lines, research has shown that military members and their families express significantly more favorable sentiments toward the police in general and greater satisfaction with the police work done in their local communities (Dai et al, 2019). Moreover, Dai et al (2019) recognize that “the police resemble the military in several ways … and therefore their social distance is slim,” likely reflecting this increased confidence (pp.…”
Section: Introductionmentioning
confidence: 99%
“…Valuable insight may be garnered when assessing the effect of social distance to police on attitudes toward policing. For instance and analogously, Dai et al . (2018) found that public satisfaction with the police is associated with having a military family member.…”
Section: Discussionmentioning
confidence: 67%
“…Finally, attitudes toward police and their services are a function of their contacts and interactions (Brown and Benedict, 2002; Cao and Wu, 2019; Dai et al ., 2018; Graziano, 2018; Graziano and Gauthier, 2017; Huang and Vaughn, 1996; Ren et al ., 2005; Schafer et al ., 2003; Weitzer and Tuch, 2002, 2005; Wozniak et al ., 2021; however, see Bolger et al ., 2021; however, see Koper et al ., 2022). Valuable insight may be garnered when assessing the effect of social distance to police on attitudes toward policing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation